The Instrumentalism of rosary in contemporary textual interpretations of muslims (2015)
This paper made an effort to examine the rosary as a spiritual instrument and one of the emblems and identifiers of Muslims world over. Not only that, the controversies expressed over its use and significance in Islam attracted a ’ research attention. Therefore, the exposition was a deliberate attempt to verify the source and the incursion of this identifier into the world of Islam. Besides, the significance of the identifier in terms of uses were subjected to juristic and holistic criticisms with the aim of differentiating the puritanical uses of the rosary from its abusive instrumentalization. The paper also did a critical assessment of texts of ahadith which scholars of Islam interpreted differently to argue on the legality or otherwise of the use of the rosary in Islam. From the findings of the study, the origin of the rosary was discovered to have predated the advent of Islam while its significance was established to have gone beyond the four walls of the mosque. As for the controversies generated among scholars concerning the position of Islam on its use, different interpretations of texts and association with diverse Muslim groups were found responsible. To some, the use of the rosary was considered an innovation while some others viewed it as Sunnah of the Prophet (S.A.W.). To some other people, its use was seen as compulsory and as an integral part .of Salat and supplication. In the concluding part of the study, it was argued that as much as the rosary is put to puritanical uses, the controversies surrounding its use are frivolous, needless and capable of creating discord among Muslims from different groups and diverse backgrounds.